Brooklyn: gendered Irish migration to the United States. Issue 4 (2nd October 2022) - Rocha, Carolina
ABSTRACT: Financed by a British-Irish-Canadian co-production, Brooklyn (John Crowley 2015) deals with twentieth-century Irish diaspora, particularly the mass emigration of unmarried Irish women in the 1950s. While Irish immigration to the United States has been ongoing since the eighteenth century, until a few decades ago the perspective of Irish women was missing in Irish and Irish-American literature and film. In the 1880–1920 period, the Bridgets, Irish-born maids, were stereotypical characters in film. In recent decades, there has been a renewed interest in filling the gap regarding the experience of Irish female immigrants, often represented as deceased mothers. Drawing upon psychoanalytical film theory and the work of cultural studies scholars who have paid special attention to the representation of Irish immigrants, this essay analyzes Brooklyn 's gendered representation of younger Irish female immigrants to the United States and the tension between nationalism and transnationalism posed by migration. This gendered depiction provides a new perspective on Irish immigration to America.